Comparison of the performance of natural latex membranes prepared with different procedures and PTFE membrane in guided bone regeneration (GBR) in rabbits - Moura, Jonas M. L.; Ferreira, Juliana F. [UNESP]; Marques, Leonardo; Holgado, Leandro; Graeff, Carlos Frederico de Oliveira [UNESP]; Kinoshita, Angela (Springer, 2014)
This work assessed the performance of membranes made of natural latex extracted from Hevea brasiliensis prepared with three different methods: polymerized immediately after collection without the use of ammonia (L1); polymerized after preservation in ammonia solution (L2); and polymerized after storage in ammonia, followed by Soxhlet technique for the extraction of substances (L3). Polytetrafluoroethylene (PTFE) membrane was used as control. Two 10-mm diameter bone defects were surgically made in the calvaria of thirty adult male New Zealand rabbits. Defects (total n = 60) were treated with guided bone regeneration (GBR) using L1, L2, L3 or PTFE membranes (n = 15 for each membrane). Ten animals were euthanized after 7, 20 and 60 days postoperatively so that five samples (n = 5) of each treatment were collected at each time, and bone regeneration was assessed microscopically. The microscopic analysis revealed defects filled with blood clot and new bone formation at the margins of the defect in all 7-day samples, while 20-day defects were mainly filled with fibrous connective tissue. After 60 days defects covered with L1 membranes showed a significantly larger bone formation area in comparison to the other groups (P < 0.05, ANOVA, Tukey). Additionally, bone tissue hypersensitization for L1 and PTFE membranes was also investigated in six additional rabbits. The animals were subjected to the same surgical procedure for the confection of one 10-mm diameter bone defect that was treated with L1 (n = 3) or PTFE (n = 3). Fifty-three days later, a second surgery was performed to make a second defect, which was treated with the same type of membrane used in the first surgery. Seven days later, the animals were euthanized and samples analyzed. No differences among L1 and PTFE samples collected from sensitized and non-sensitized animals were found (P > 0.05, Kruskal-Wallis). Therefore, the results demonstrated that latex membranes presented performance comparable to PTFE membranes, and that L1 membranes induced higher bone formation. L1 and PTFE membranes produced no hypersensitization in the bone tissue.